Determining the Problems of Management Shareholding and the Mixed Ownership - Gao Li; Song Shanshan (Modern Perspectives in Economics, Business and Management Vol. 7, 2021)
In recent years, managerial ownership has begun to be used as an incentive mechanism in China. Managerial ownership is one of the ways to realize the mixed ownership reform of state owned enterprises. Taking the mixed ownership reform of Chinese state-owned enterprises as the research object, this paper analyzes the impact of management ownership on the performance of mixed ownership enterprises. The conclusions are as follows: management ownership and corporate performance have a positive correlation in state-owned listed companies. The financial performance of the company increases with the proportion of management shareholding, ownership concentration and equity balance. There is a significant negative correlation between the proportion of independent directors and the rate of return on net assets, which shows that the independent directors of state-owned enterprises in China have not played their due role in the governance of state-owned enterprises.